Penerapan Demokrasi Pancasila di Indonesia - Riadhul Fadilah; Alikha Naya Dwi Azkhia; Dzira Vania Putri Purnomo; Zaenul Slam (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
Democracy is a system of government that places the people as the highest authority in political decision-making. The concept of democracy is not only related to electoral mechanisms, but also includes values such as freedom, equality, participation, and respect for human rights. This paper aims to comprehensively examine the meaning of democracy, its defining characteristics, the aspects that shape the democratic system, its fundamental principles, and its implementation in national and civic life. The characteristics of democracy can be seen in the existence of popular sovereignty, government based on the rule of law, and the protection of citizens’ rights. The aspects of democracy include political, legal, and social dimensions that are interconnected. Democratic principles such as freedom of expression, equality before the law, and active public participation serve as the main foundation in its practice. In its implementation, democracy requires a balance between the rights and obligations of citizens, as well as an active role of the government in ensuring justice and welfare. Therefore, democracy is expected to create a just, prosperous, and civilized society.